Atomistic mechanisms of calcium permeation modulated by Q/R editing and selectivity filter mutations in GluA2 AMPA receptors - Florian Heiser; Johann Biedermann; Ece Kuru; Andrew J. R. Plested; Han Sun (Proceedings of the National Academy of Sciences, 2025)
GluA2 is a key subunit of α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) ion channels that is abundantly expressed in the vertebrate brain. Posttranscriptional Q/R editing of GluA2 renders AMPARs nearly impermeable to calcium ions, which is crucial for their normal function. Although previous studies have characterized conductivity and selectivity differences between edited and unedited GluA2 variants and heteromeric receptors incorporating GluA2, the consequences of pore editing have not been studied in all-atom simulations, which leave the atomistic mechanisms unclear. In this study, we investigate ion permeation in the context of multiple Ca 2+ binding sites along the pore predicted from molecular dynamics (MD) simulations, considering both mutations and co-permeating monovalent ions. Patch clamp electrophysiology recordings confirmed a binding site at the intracellular mouth of the selectivity filter that confers selectivity for calcium over monovalent ions. A patient mutation at the same site has been previously shown to cause neurodevelopmental abnormalities. Furthermore, MD simulations of GluA2 with different arginine copy number at the Q/R site show that Ca 2+ conduction is blocked in the presence of two arginines, whereas K + is only blocked by four arginines, in explaining the results from decades of electrophysiological work. Finally, MD simulations revealed that Ca 2+ reduces K + conduction by preferentially occupying the intracellular selectivity filter binding site, whereas Na + does not. This result is consistent with electrophysiological results from the D590 mutants and suggests that divalent binding in the selectivity filter is a major determinant of AMPAR conductance.